Positions constructed for a female therapist in male batterers' treatment groups - Päivinen, Helena (2010)
The aim of this study was to examine how male batterers regard to a female therapist in their group treatment. Of interest were the socially constructed positions for a female therapist. This study intends to examine what kind of positions the batterers construct for a female therapist in their speech and how the female therapist reacts to invitations to take up these positions. Attention was paid also to the male therapist’s positions in these situations. The topic was approached from a social constructionist and discourse analytic point of view and Grounded Theory was used as the method of analysing the data.